2006
DOI: 10.1001/archneur.63.6.895
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Surgical Treatment of De Novo, Adult-Onset, Cryptogenic, Refractory Focal Status Epilepticus

Abstract: Background: There have been few published reports of successful surgical treatment of focal status epilepticus. Surgical intervention is considered a last resort after medical strategies have been exhausted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 14 publications
0
32
0
4
Order By: Relevance
“…A retrospective study reported similar SE resolution in three patients who underwent either a cortical resection and multiple subpial transactions, completion of a callosotomy, or an anterior 2/3 callosotomy, followed by focal resection for recurrent SE [45]. In other case reports, cessation of SE was accomplished through single or consecutive treatments with these procedures [46][47][48][49][50].…”
Section: Surgerymentioning
confidence: 91%
“…A retrospective study reported similar SE resolution in three patients who underwent either a cortical resection and multiple subpial transactions, completion of a callosotomy, or an anterior 2/3 callosotomy, followed by focal resection for recurrent SE [45]. In other case reports, cessation of SE was accomplished through single or consecutive treatments with these procedures [46][47][48][49][50].…”
Section: Surgerymentioning
confidence: 91%
“…It is possible that the majority or even all patients with epilepsia partialis continua on invasive EEG monitoring would show similar PLEDs over the focal motor area of origin, thus ending any persistent debate as to their cortical origin. Several authors have discussed factors that determine the timing of surgical intervention for status epilepticus, and although probably not yet a mainstream consideration in the treatment of refractory status epilepticus, there certainly is a growing awareness and literature for consideration of this ''new,'' highly effective treatment option [9,16,[19][20][21][22][23][24][25][26][27]. Table 1 summarizes the previously published 30 cases of different neurosurgical procedures performed, including vagus nerve stimulation (in two patients) for various forms of status epilepticus and different etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple case series subsequently documented the role of surgical intervention for RSE. 1,3,4,[9][10][11][12]16,17,19,20,22,24,27 Interventions included focal cortical resection, hemispherectomy, MST, vagus nerve stimulation, and callosotomy. Ng et al 20 described 5 patients with RSE successfully treated with neurosurgical intervention: 3 who underwent focal cortical resection and 1 each who underwent hemispherectomy and transcallosal resection of a hypothalamic hamartoma.…”
Section: Van Nessmentioning
confidence: 99%
“…Studies on the surgical treatment of RSE are therefore limited to single case reports or small series involving cortical resection, callosal sectioning, multiple subpial transections (MSTs), hemispherectomy, and vagus nerve stimulation. 1,3,4,[9][10][11][12]16,17,19,20,24 There is no consensus on how or when to surgically manage this medical emergency. Object.…”
mentioning
confidence: 99%